Mother Tongue and the Origins of Nationalism: (A Comparative Analysis of the Armenian and European Primary Sources)* - Ayvazyan, Armen (Armenian Folia Anglistika, 2006)
The article offers a comparative analysis of the data in Armenian, English, French and Russian sources trying to comment on the political and social settings in which a native language becomes a subject of nationwide love and pride. The author concludes that it happens when an ethnic group, which has already attained a high level of cultural awareness, adopts consistent and stable features typical of a nation. Later, with the support of the political elite, the intelligentsia carries out the further elaboration of the national self-consciousness which, in its turn, aims to analyze the elements of the national identity (including the national language) and to give theoretical and ideological explanations substantiating their necessity and efficiency. The author of the article states that as far back as the 5th century the Armenian intelligentsia highly regarded the cultural and political and strategic significance of the Armenian Language. Following the observations made by Pavstos Byuzand, Movses Khorenatsi and Yeghishe, the author comments on the clarity of the Armenian national self-consciousness and the high level of ideologization of the Armenian political thought. * This is an abridged version of the study with the same title that was originally published by the author in Armenian as Mayreni lezun yev azgaynakanutian skzbnavorume. haykakan yev yevropakan skzbnaghbyurneri hamematakan knnutiun (Yerevan, Matenadaran: Artagers, 2001, the updated 2nd ed. was published in 2004).